Striatal Dopamine Transporter Function Is Facilitated by Converging Biology of α-Synuclein and Cholesterol - Threlfell, Sarah; Mohammadi, Amir Saeid; Ryan, Brent J.; Connor-Robson, Natalie; Platt, Nicola J.; Anand, Rishi; Serres, Florence; Sharp, Trevor; Bengoa-Vergniory, Nora; Wade-Martins, Richard; Ewing, Andrew; Cragg, Stephanie J.; et al. (Frontiers in Cellular Neuroscience, 2021)
Striatal dopamine transporters (DAT) powerfully regulate dopamine signalling, and can contribute risk to degeneration in Parkinson’s disease (PD). DATs can interact with the neuronal protein α-synuclein, which is associated with the aetiology and molecular pathology of idiopathic and familial PD. Here, we tested whether DAT function in governing dopamine (DA) uptake and release is modified in a human-alpha-synuclein-overexpressing (SNCA-OVX) transgenic mouse model of early PD. Using fast-scan cyclic voltammetry (FCV) in ex vivo acute striatal slices to detect DA release, and biochemical assays, we show that several aspects of DAT function are promoted in SNCA-OVX mice. Compared to background control alpha-synuclein-null mice (snca-null), SNCA-OVX mice have elevated DA uptake rates, and more pronounced effects of DAT inhibitors on evoked extracellular DA concentrations ([DA]o) and on short-term plasticity (STP) in DA release, indicating DATs play a greater role in limiting DA release and in driving STP. We found that DAT membrane levels and radioligand binding sites correlated with alpha-synuclein level. Furthermore, DAT function in snca-null and SNCA-OVX mice could also be promoted by applying cholesterol, and using Tof-SIMS we found genotype-differences in striatal lipids, with lower striatal cholesterol in SNCA-OVX mice. An inhibitor of cholesterol efflux transporter ABCA1 or a cholesterol chelator in SNCA-OVX mice reduced the effects of DAT-inhibitors on evoked [DA]o. Together these data indicate that human alpha-synuclein in a mouse model of PD promotes striatal DAT function, in a manner supported by extracellular cholesterol, suggesting converging biology of alpha-synuclein and cholesterol that regulates DAT function and could impact on DA function and PD pathophysiology.